2020
DOI: 10.1002/cad.20368
|View full text |Cite
|
Sign up to set email alerts
|

Changing self‐control: Promising efforts and a way forward

Abstract: Researchers have long known that self-control, or impulse control, is important for a variety of life outcomes, including health, education, and behavior. In criminology, the most popular perspective on self-control argues that it is a multidimensional trait that is relatively stable after about age 8. Some work, however, has shown that in fact, self-control may not be as stable as originally thought. This article examines the evidence on interventions seeking to enhance self-control and subsequently to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…These changes are theoretically related to components of psychosocial maturation (e.g., responsibility). The importance of temperance in reducing victimization risk aligns with evidence on the success of programs aimed at reducing impulsivity and sensation seeking (Piquero & Rocque, 2020;Piquero et al, 2016;Romer et al, 2010). Given the generally high risk of victimization among adolescents, school-wide programs targeting risky behaviors may also be effective if peers take a leadership role and encourage non-risky behavior (Campbell et al, 2008;Paluck et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…These changes are theoretically related to components of psychosocial maturation (e.g., responsibility). The importance of temperance in reducing victimization risk aligns with evidence on the success of programs aimed at reducing impulsivity and sensation seeking (Piquero & Rocque, 2020;Piquero et al, 2016;Romer et al, 2010). Given the generally high risk of victimization among adolescents, school-wide programs targeting risky behaviors may also be effective if peers take a leadership role and encourage non-risky behavior (Campbell et al, 2008;Paluck et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…However, intervention research points to parent marital relationship satisfaction, and not child effortful control, as a modifiable factor. That is, despite increasing research on psychosocial interventions for modifying child and adolescent effortful control, support for the efficacy of these approaches remains limited [52]. Yet, there is a robust evidence base for psychosocial interventions to support marital relationship quality [53], which might be translated into the type 1 diabetes context.…”
Section: Associations Of Parent Neuroticism and Child Effortful Contr...mentioning
confidence: 99%
“…While self-control theory widely applied in criminology (Gottfredson & Hirschi, 1990) demonstrates cross-cultural applicability (Vazsonyi et al, 2021), and low self-control has serious social consequences (Burt, 2020), it is not itself a permanent trait but a 'set of skills, capacities, and behaviors that we need to 'operate' in a self-regulation feedback loop' (Gillebaart, 2018, p. 4). Program interventions that improve self-control are considered an integral aspect of reducing crime, delinquency, and promoting overall health outcomes (Piquero & Rocque, 2020). While Kelley et al, (2021) found a significant decrease in low self-control for men incarcerated for sexual violence offenses, mediation analysis was not conducted.…”
Section: Introductionmentioning
confidence: 99%